Differences in Satisfaction Level between Subsidised JKN Patients and Non-Subsidised JKN Patients: A Case Study in a Hospital in Bantul with Quantitative Analysis Approach - Yanasta Yudo Pratama; Muhammad Syamsu Hidayat; Tri Ani Marwati; Lina Handayani (Rumah Sakit Akademik Universitas Gadjah Mada, 2022)
ABSTRACTIntroduction: The National Health Insurance (JKN) organized by BPJS is a guarantee in the form of health protection so that participants get the benefits of health checks and protection in meeting basic health needs given to everyone. Measuring the level of patient satisfaction is needed to determine the level of service provided by a service provider. To identify differences in the satisfaction of JKN class 3 PBI patients and JKN class 3 non PBI patients who received health services at the place research.Materials and Methods: This study used an analytical observational research design with a cross sectional method through a Quantitative Method approach. Data obtained by using questionnaires and interviews with respondents. The level of patient satisfaction was analyzed using GAP scores, CSI, and Independent Samples T Test.Results: The results of the GAP score indicate that JKN class 3 PBI patients have the lowest GAP score on the reliability dimension, which is -0.1733 and the highest GAP score on the assurance dimension with a score of -0.0875. Meanwhile, JKN class 3 non-PBI patients had the lowest score on the tangibles dimension with -0.1955 and the highest on the reliability dimension with -0.1711. JKN class 3 PBI patients had a CSI score of 69.81% and JKN class 3 non-PBI patients had 66.938%. If statistically tested, there is a significant difference between JKN class 3 PBI patients and JKN class 3 non-PBI patients with p value < 0.05.Conclusion: From the results of the analysis, at the placed research patients are generally satisfied with the services provided. JKN class 3 PBI patients feel more satisfied than JKN class 3 non PBI patients.